1988
DOI: 10.1016/0014-5793(88)80461-7
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic properties of polyphenoloxidase in organic solvents A study in Brij 96‐cyclohexane reverse micelles

Abstract: Polyphenoloxidase entrapped in Brij 96-cyclohexame reverse micelles showed both cresolase activity towards monophenols and catecholase activity towards diphenols. The kinetic parameters, such as apparent K,,,, temperature effect and pH profile, were determined for catecholase activity, the findings being very close to those found in aqueous systems. The enzyme activity was dependent on the molecular ratio of water to surfactant (o,), obtaining a maximum activity at o, = IO. The stability of the system with tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…The enzyme concentration used in each medium was 1.5 ,tg/ml. [7]. 0.5 t Activity measured in Brij 96/cyclohexane reverse micelles (JW.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme concentration used in each medium was 1.5 ,tg/ml. [7]. 0.5 t Activity measured in Brij 96/cyclohexane reverse micelles (JW.…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenol oxidase activity was also measured in 50 mM-Mes buffer, pH 6.0, at 20°C and in Brij 96/cyclohexane reverse micelles [water/surfactant molar ratio (W.) = 12] by using previously described methods [7,9].…”
Section: Enzyme Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this problem, the addition of some non‐ionic surfactants such as Tween 85 (polyoxyethylene sorbitan trioleate) to the AOT reverse micellar systems was proposed and proved to be very effective by a number of researchers9–13 and also by our group 14. It has been shown that Tween 85 effectively reduces the surface charge density and the hydrophobicity of AOT reverse micelles by adsorption at the water–oil interface 12–14…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosinase is an enzyme that has drawn attention due to its application in enzyme biosensors for the detection of phenolic pollutants. This enzyme is one of the first that has been proven to function in reversed micelles, such as those formed by AOT surfactant in isooctane [91], cyclohexane [92], and hexane [93] and others composed of nonionic Brij96 (poly-(10)-oxyethylene oleyl ether) in cyclohexane [94]. Yang and Robb [95] studied two different microemulsions composed of AOT and isooctane and CTAB, hexane and chloroform, where mushroom tyrosinase was immobilized and effectively used to catalyze the formation of o-quinones by oxidation of o-diphenols and presented superactivity in AOT microemulsion.…”
Section: Tyrosinasementioning
confidence: 99%